Contextual factors and motivations affecting rural community sanitation in low- and middle-income countries: A systematic review - Novotný, Josef; Hasman, Jiří; Lepič, Martin (International journal of hygiene and environmental health, 2018)
BACKGROUND: Unsafe management of human faecal waste represents a major risk for public health, particularly in low- and middle-income countries. Efforts to improve sanitation conditions are considerably sensitive to contextual specifics of natural and social environments. This review operationalises, analyses, and synthesises evidence of how contextual factors and motivations affect different sanitation outcomes with a specific focus on community approaches to rural sanitation. METHODS AND FINDINGS: We operationalised contextual factors and motivations as determinants that influence sanitation conditions independently of the examined intervention. We conducted a systematic search of both peer-reviewed and grey literature with no restriction on the methods After screening the titles and abstracts of 19,198 records obtained through initial searches, we scrutinised the full content of 621 studies for relevance. While 102 of these studies qualified to be assessed for risk of bias and information content, ultimately, just 40 studies met our eligibility criteria. Of these 40 studies from 16 countries, 26 analysed specific interventions and 14 were non-interventional. None of the experimental studies reported the effects of contextual factors or motivations as operationalised in this study and only observational evidence was thus used in our review. We found that sanitation interventions are typically seen as the principal vehicles of change, the main instruments to fix 'deviant' behaviour or ensure access to infrastructure. The programmatic focus of this study on sanitation determinants that act independently of specific interventions questions this narrow understanding of sanitation dynamics. We identified 613 unique observations of quantitatively or qualitatively established relationships between certain contextual factors or motivations and 12 different types of sanitation outcomes. The sanitation determinants were classified into 77 typologically similar groups clustered into 12 broader types and descriptively characterised. We developed a graphical synthesis of evidence in the form of a network model referred to as the sanitation nexus. The sanitation nexus depicts how different groups of determinants interlink different sanitation outcomes. It provides an empirically derived conceptual model of sanitation with an aggregate structure indicating similarities and dissimilarities between sanitation outcomes with respect to how their sets of underlying determinants overlap. CONCLUSION: This study challenged the understanding of context as merely something that should be controlled for. Factors that affect targeted outcomes independently of the analysed interventions should be scrutinised and reported. This particularly applies to interventions involving complex human-environment interactions where generalisability is necessarily indirect. We presented a novel approach to comprehending the contextual factors and motivations which influence sanitation outcomes. Our approach can be analogously applied when mapping and organising underlying drivers in other areas of public and environmental health. The sanitation nexus derived in this study is designed to inform practitioners and researchers about sanitation determinants and the outcomes they influence.
Keywords: veřejné zdravotnictví; Motivations; sanitace; Intervention; Context; lidé; Public Health; Humans; Waste Management; Systematic review; nakládání s odpady; venkovské obyvatelstvo; Socioeconomic Factors; motivace; Developing Countries; rozvojové země; socioekonomické faktory; Rural sanitation; Rural Population; Sanitation; Motivation; Community sanitation